The Effect of Role-Playing Learning Model in Improving Descriptive Writing Skills Among Mild Intellectually Disabled Students in Grade XII at SLB Negeri Cilacap - Hidayat, Rochmat; Septiana, Fajar Indra (Journal of English Language and Education, 2025)
This study aims to determine the effectiveness of the role-playing learning model in improving descriptive writing skills in mildly mentally disabled students in grade XII at SLB Negeri Cilacap. The background of this study stems from the challenges faced by children in gathering ideas and expressing them in writing due to cognitive and adaptive limitations. The objective of this study is to examine the effect of implementing a role-playing learning model on improving descriptive essay writing skills among Grade XII students with mild intellectual disabilities at Cilacap State Special School. The method used was a quantitative approach with a Single Subject Research (SSR) design using an A-B-A design. Data collection techniques were conducted through direct observation and performance tests in three stages, namely baseline 1 (A1), intervention (B), and baseline 2 (A2). The results showed that during the intervention phase, there was an improvement in the children's ability to gather ideas, use appropriate vocabulary, and describe objects clearly. Data analysis revealed significant differences between the pre- and post-intervention phases. In conclusion, the role-playing learning model is effective in improving descriptive writing skills among children with mild intellectual disabilities, as well as enhancing their motivation and active participation in the learning process.